2017
DOI: 10.1002/cpt.688
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Small Molecule and Biological Therapeutic Approaches in the Treatment of Psoriasis

Abstract: New treatments continue to be developed for psoriasis. In this review, we aim to summarize the results of the major published studies on biologic and small molecule drugs for the treatment of psoriasis. We emphasize the safety, efficacy, and tolerability of these treatment options. A review of the MEDLINE database was conducted for each class of medication. Randomized controlled trials were identified for each medication; data on efficacy, safety, and tolerability were reviewed. Biologic and small molecule tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 88 publications
(213 reference statements)
1
7
0
Order By: Relevance
“…49 Thus, small molecule inhibitors or monoclonal antibodies targeting these cytokines have been used in the clinical treatment of both skin and joint manifestations of psoriasis. 50,51 In this study, we observed that oral administration of GL attenuated TNF-, IL-6, IL-17A/F, IL-22, and IL-23 production in skin lesions induced by IMQ (Fig. 3).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…49 Thus, small molecule inhibitors or monoclonal antibodies targeting these cytokines have been used in the clinical treatment of both skin and joint manifestations of psoriasis. 50,51 In this study, we observed that oral administration of GL attenuated TNF-, IL-6, IL-17A/F, IL-22, and IL-23 production in skin lesions induced by IMQ (Fig. 3).…”
Section: Discussionsupporting
confidence: 54%
“…It is known that production of TNF‐α, IL‐6, IL‐17A/F, IL‐22, and IL‐23 is elevated in both the skin and synovium of psoriatic patients . Thus, small molecule inhibitors or monoclonal antibodies targeting these cytokines have been used in the clinical treatment of both skin and joint manifestations of psoriasis . In this study, we observed that oral administration of GL attenuated TNF‐α, IL‐6, IL‐17A/F, IL‐22, and IL‐23 production in skin lesions induced by IMQ (Fig.…”
Section: Discussionmentioning
confidence: 51%
“…In this issue, Turberville et al . summarize recent advances in the pharmacological treatment of psoriasis . Generally considered an autoimmune disease, psoriasis is a chronic skin condition that affects 2–3% of the population.…”
Section: Skin Diseasesmentioning
confidence: 99%
“…In this issue, Turberville et al summarize recent advances in the pharmacological treatment of psoriasis. 10 Generally considered an autoimmune disease, psoriasis is a chronic skin condition that affects 2-3% of the population. Hyperproliferation of keratinocytes, resulting in scaly skin and plaque formation, causes a disruption of the skin barrier which can be severely painful, debilitating, and prone to infections.…”
Section: Skin Diseasesmentioning
confidence: 99%
“…These agents are associated with an increased risk of infections, though mostly tend to be mild infections. The use of biological agents has certain contraindications and the risks of infection along with long-term usage may potentially lead to tumorigenesis in patients with active pulmonary tuberculosis, advanced congestive heart failure, hepatitis B infection, or demyelination diseases, including multiple sclerosis (Turbeville et al, 2017). Drug resistance and disease recurrence along with unintentional disruption of other pathways are a few shortcomings involved with the usage of biological agents (Reich et al, 2005).…”
Section: Introductionmentioning
confidence: 99%